2020
DOI: 10.1016/j.omtn.2020.01.024
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Exosome miR-155 Derived from Gastric Carcinoma Promotes Angiogenesis by Targeting the c-MYB/VEGF Axis of Endothelial Cells

Abstract: Exosomes, membranous nanovesicles, naturally carry proteins, mRNAs, and microRNAs (miRNAs) and play important roles in tumor pathogenesis. Here we showed that gastric cancer (GC) cell-derived exosomes can function as vehicles to deliver miR-155 to promote angiogenesis in GC. In this study, we first detected that the expression of miR-155 and c-MYB was negatively correlated in GC and that c-MYB was a direct target of miR-155. We next characterized the promotional effect of exosome-delivered miR-155 on angiogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…In addition, miR-155 has been con rmed as "oncomiR'' in virious cancer types, including lymphoma, gastric cancer and breast cancer [24]. More importantly, recent work in our laboratory reported that GC exosomal miR-155 could promote angiogenesis through targeting c-MYB and FOXO3 [25,26]. According to our clinical results, we have con rmed that adipo-differentiation was blocked by upregulating miR-155 in A-MSCs obtained from GC patients.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, miR-155 has been con rmed as "oncomiR'' in virious cancer types, including lymphoma, gastric cancer and breast cancer [24]. More importantly, recent work in our laboratory reported that GC exosomal miR-155 could promote angiogenesis through targeting c-MYB and FOXO3 [25,26]. According to our clinical results, we have con rmed that adipo-differentiation was blocked by upregulating miR-155 in A-MSCs obtained from GC patients.…”
Section: Discussionsupporting
confidence: 64%
“…The involvement of miR-23a in angiogenesis has also been demonstrated in hypoxic HCC [ 172 ]. It has been shown that exosomes containing miR-155 secreted by gastric cancer (GC) cells significantly increase the rate of tumor angiogenesis by enhancing the expression of VEGF [ 173 ]. Skin cancer-derived exosomes and melanoma-derived exosomes can promote angiogenesis by delivering miR-9 to endothelial cells and activating the JAK–STAT pathway [ 174 , 175 ].…”
Section: Tumor-derived Exosomes In Angiogenesismentioning
confidence: 99%
“…Other EEVs from human CD34-positive stem cells containing high levels of pro-angiogenic miRNAs (miR-126 and miR-130a) conferred in vivo angiogenesis ability and led to the in vitro formation of vessel-like endothelial structures of HUVECs [122]. EEVs derived from a gastric cancer patient contained miRNA155, which negatively regulates C-MYB and in turn promotes angiogenesis via VEGF [123]. The CD105-positive EEVs expressing a set of pro-angiogenic miRNAs, such as VEGF, FGF2, MMP-2, and MMP-9, mediate an angiogenic phenotype and induce vessel formation in SCID mice [121].…”
Section: Cancer Eevs Promote Neoangiogenesismentioning
confidence: 99%